Paratesticular Tumors: A Report of Two Rare Cases - M, Sinchana K; Jadhav, Meena N; Datar, Rujutha; Kittur, Shreekant K (Annals of Pathology and Laboratory Medicine, 2019)
Paratesticular tumors are rare comprising 7-10% of total intrascrotal tumors of which 70% are benign and 30% are malignant. Leiomyomas and undifferentiated pleomorphic sarcomas are two such rare paratesticular tumors which should be accurately diagnosed for purpose of treatment and prognosis. We report here two cases. In first case, a 65-year-old man presented with paratesticular mass of 12 years duration. Histology showed features of benign spindle cell tumor. On immunohistochemistry the tumor cells were positive for vimentin, desmin, h-caldesmon and SMA. Based on these findings a diagnosis of leiomyoma of scrotum was made. In second case, a 66-year-old male presented with left paratesticular mass of eight months duration. Histology showed features of high-grade sarcoma. On immunohistochemistry tumor cells were focally positive for SMA and negative for h-caldesmon, desmin, calretinin and ALK-1. A final diagnosis of undifferentiated pleomorphic sarcoma of paratesticular region, grade 3/3 was made.